BONE AND ARTICULAR IMPAIRMENT IN TUBERCULOSIS. AN IMPORTANT EXTRAPULMONARY INVOLVEMENT: A REVIEW - Vieira Teles Filho, Ricardo; de Matos Abe, Guilherme; Henrique Souza de Azevêdo, Lucas; Carrijo Melo, Nilo; Fouad Rabahi, Marcelo; Tavares Daher, Murilo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
This is a literature review on the pathogenesis and epidemiology of bone tuberculosis (BTB). Full-text papers from 2001 to 2017 were included. After inclusion criteria were met, 23 papers were selected for analysis. Results show that in most cases of BTB, the spine is the main site involved, regardless of the geographical regions analyzed; hip and knee involvement are also frequent. These three sites are the most prevalent, totaling approximately 70 - 80% of infections. The major forms of involvement are tuberculous spondylitis, tuberculous osteomyelitis, primarily in areas of long-bone growth, as well as cases of chronic disease leading to tuberculous arthritis, mainly in endemic areas. The results also indicated that bone involvement is still prevalent, being the fifth cause of extrapulmonary disease involvement in Brazil. This review highlights the role of tuberculosis in public health, especially in economically active groups where BTB is most prevalent.